(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , GHf TGcQ J (B764 (3g` s
(3ChdgG (B:s
(3jHOC ef SfI (B80(3g` s
(3BNQgG (B:s
(3jfJgi SfI (B123(3g` s
(3fSNI SGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B219 s
(3eUOQ GbJfGA GdCUd (B:s
(3HGQjS (B(1587) s
Keywords: (3GdJGQjNs